Prenatal Environment and Neurodevelopmental Disorders - Doi, Miyuki; Usui, Noriyoshi; Shimada, Shoichi (Frontiers in Endocrinology, 2022)
The internal and external environment of the mother during the developmental stages of the fetus affects the offspring’s health. According to the developmental origins of health and disease (DOHaD) theory, environmental factors influence the offspring and also affect health in adulthood. Recently, studies based on this theory have gained attracted attention because of their clinical utility in identifying the risk groups for various diseases. Neurodevelopmental disorders (NDDs) such as autism spectrum disorder (ASD) and attention-deficit hyperactivity disorder (ADHD) can be caused by exposure to certain prenatal environments during pregnancy. This review describes the latest findings on the effect of prenatal environment on the onset mechanism of NDDs based on the DOHaD theory. Unravelling the molecular mechanisms underlying the pathogenesis of NDDs is important, because there are no therapeutic drugs for these disorders. Furthermore, elucidating the relationship between the DOHaD theory and NDDs will contribute to the popularization of preventive medicine.